Design for additive manufacturing of mechanical connections toward hybrid products - Sampaio, Álvaro M. (2020)
Improving additive manufacturing (AM) products is important since these technologies still have some limitations that restrict production. These limitations are associated with the size of the build envelope, the materials available and the possibility of multi-material fabrication. For this particular case, there are two different strategies: (i) one, is to build fittings that can act as mechanical connections for different parts, or (ii), to embed the parts as external components in the AM build process of the fittings. This paper presents exploratory research to quickly improve AM ceramic products by AM polymeric fittings in the two strategies presented. The overall aim is to describe a methodology that can optimize products using AM material extrusion technology and that can be used for the production of hybrid products.